The Concept of ‘Junction Area’ – Sui Generis Solution to Reconciling the Integrity of Territorial Sea and ‘Freedoms of Communication’? - Fabijanić Gargo, Sandra (Pécs journal of international and European law, 2020)
The rendering of the Final Award in the arbitration proceeding between Croatia and Slovenia in June 2017 immediately triggered the rise of a new and still ongoing dispute. Croatia does not ac- cept the application of the Award and refuses to implement it, claiming that the arbitration process was irreversibly compromised; Slovenia, on the other hand, insists on the Award’s implementation. The focus of this Article is not on the deeper elaboration of the Final Award, but rather on the ex- amination of the ‘Junction area’ concept, which has been introduced by the Award. It represents a unique and challenging regime of a ‘freedoms of communication’ that is to be implemented in part of the Croatian territorial sea with the purpose of reconciling both the Slovenian request for access to the High Seas and the Croatian sovereignty in its territorial sea.